Synthesis and antitumoral evaluation of natural product‐like compounds based on tropolone and benzotropolone derivatives. Issue 3 (8th December 2022) - Eugui, Macarena; Lucero, Valeria; do Carmo, Hugo; Cabrera, Mauricio; Moyna, Guillermo
Abstract: We present the preparation of a series of novel natural product‐like homobarrelenones, norcaranes, and dihydrofluorenones through a diversity‐oriented synthetic (DOS) strategy that combines Diels–Alder reactions and phototransformations, as well as their biological evaluation against MCF‐7, HT‐29, and NCI‐H460 human tumor cells. Six of these demonstrated activities in the micromolar range against the three cell lines, and none were predicted as cytotoxic against human nontumor cells according to in silico studies. In addition, within the set of active derivatives, three exhibited low unspecific cytotoxicity in a sperm motility assay. The rich functionality of the new compounds makes them ideal candidates for exhaustive structure–activity relationship studies. Abstract : Novel natural product‐like homobarrelenones, norcaranes, and dihydrofluorenones, several with micromolar antitumoral activity and no predicted cytotoxicity, were prepared through a diversity‐oriented synthetic strategy combining Diels–Alder reactions and phototransformations.